A CCR5+ memory subset within HIV-1-infected primary resting CD4+ T cells is permissive for replication-competent, latently infected viruses in vitro - Terahara, Kazutaka; Iwabuchi, Ryutaro; Hosokawa, Masahito; Nishikawa, Yohei; Takeyama, Haruko; Takahashi, Yoshimasa; Tsunetsugu-Yokota, Yasuko (BMC research notes, 2019)
Resting CD4 T cells are major reservoirs of latent HIV-1 infection, and may be formed during the early phase of the infection. Although CCR5-tropic (R5) HIV-1 is highly transmissible during the early phase, newly infected individuals have usually been exposed to a mixture of R5 and CXCR4-tropic (X4) viruses, and X4 viral DNA is also detectable in the host. Our aim was to identify which subsets of resting CD4 T cells contribute to forming the latent reservoir in the presence of both X4 and R5 viruses. Primary resting CD4 naïve T (T ) cells, CCR5 memory T (T ) cells, and CCR5 T cells isolated by flow cytometry were infected simultaneously with X4 and R5 HIV-1, which harbored different reporter genes, and were cultured in the resting condition. Flow cytometry at 3 days post-infection demonstrated that X4 HIV-1 cells were present in all three subsets of cells, whereas R5 HIV-1 cells were present preferentially in CCR5 T cells, but not in T cells. Following CD3/CD28-mediated activation at 3 days post-infection, numbers of R5 HIV-1 cells and X4 HIV-1 cells increased significantly only in the CCR5 T subset, suggesting that it provides a major reservoir of replication-competent, latently infected viruses.